Frequency of Caesarean Hysterectomy in Patients with Placenta Previa - Sarfraz, Rehana; Haq, Bushra; Jabbar, Hira; Muhammad Ahmad (Indus Journal of Bioscience Research, 2025)
Objective: To determine the association of cesarean hysterectomy with placenta previa and placenta accrete spectrum. Study design: Prospective Cohort study. Place and Duration of Study: Department of Obstetrics and Gynaecology, Services Hospital, Lahore, From January 2025 to June 2025. Methodology: Out of n=170 females aged 20–40 with gestational age between 32-37 weeks, divided into two groups. After informed consent, demographic and obstetric details were recorded. All participants underwent standardized abdominal ultrasound by a senior radiologist to confirm the presence or absence of placenta previa or Placenta accrete spectrum. Patients were categorized into exposed (with placenta previa/PA) n=85 and unexposed (without placenta previa/PAS) groups n=85. All underwent cesarean section. Cesarean hysterectomy was performed in cases with life-threatening postpartum hemorrhage unresponsive to conservative measures. Descriptive statistics were used to describe baseline characteristics. Relative risk was calculated to measure the association of cesarean hysterectomy with placenta previa or placenta accrete spectrum. RR>1 was taken as significant. Stratified analysis was performed for age, BMI, parity, gestational age and number of previous cesarean sections to assess effect modifiers on the association between placenta previa/PAS and cesarean hysterectomy. Results: Cesarean hysterectomy occurred in 20% of patients with placenta previa or Placenta accrete spectrum compared to 2.4% in those without, yielding a relative risk of 8.5. Stratified analysis showed stronger associations in patients with higher BMI, parity ≥3, and ≥2 previous cesarean sections. Conclusion: Cesarean hysterectomy was significantly more frequent in patients with placenta previa or accreta spectrum, highlighting the need for early identification and preparedness in high-risk pregnancies.